The Impact of Chronic Diseases on the Quality of Life of Primary Care Patients in Cambodia, Myanmar and Vietnam - Supa PENGPID; Karl PELTZER (Tehran University of Medical Sciences, 2018)
Background: Quality of life is a key measure in estimating the burden of disease, especially of chronic diseases. This study investigated the impact of a variety of chronic diseases on quality of life (QoL) in primary health care patients in three Southeast Asian countries (Cambodia, Myanmar, and Vietnam). Methods: This cross-sectional survey was conducted on 4803 adult chronic disease patients (mean age 49.3 yr; SD=16.5) recruited systematically from primary health care centers in rural and urban areas in Cambodia, Myanmar and Vietnam in 2015. Results: In ANCOVA analysis, adjusted for age, sex, marital status, geo locality, education, income and country, the poorest summative QoL was found among patients with cancer (49.8 mean score), followed by Parkinson's disease (50.7), mental disorder (53.2), epilepsy (53.3), asthma (54.3), kidney disease (54.3), chronic obstructive pulmonary disease (COPD) (54.5) and cardiovascular diseases (CVD) (55.1). Patients having three or more chronic conditions had a significantly lower summative QoL than patients with two chronic conditions (56.4) and one chronic condition (58.0). In multivariable linear regression analysis, younger age, being married or cohabitating, better education, living in an urban area, having only one chronic condition, not experiencing chronic disease stigma and good medication adherence was associated with better QoL in two or three of the study countries. Conclusion: Major chronic diseases were found to have poor QoL. The determined QoL of chronic disease patients in this study provides information to improve the management of chronic diseases.